Q: Solve for x: 5 (x + 2) = 4 ( x + 3)

A: 5(x + 2) = 4(x + 3) 5x + 10 = 4x + 12; 5x - 4x = 12 - 10; x = 2

Expert answered|julvan.weegy|Points 56|

Question

Asked 7/21/2012 8:54:56 AM

Updated 6/21/2015 5:46:13 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

3

5(x + 2) = 4(x + 3)

5x + 10 = 4x + 12;

5x - 4x = 12 - 10;

x = 2

5x + 10 = 4x + 12;

5x - 4x = 12 - 10;

x = 2

Added 6/21/2015 7:46:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [6/21/2015 11:44:55 AM]

simpify 2x+6+5x-3

Question

Expert Answered

Updated 8/6/2014 12:23:39 AM

4 Answers/Comments

(96xy^20)(3x^3y) = 288x^4y^21

Added 8/5/2014 9:30:56 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [8/5/2014 11:00:42 PM]

I tried to unflag this answer but its not available. Weird.

Anyone can help?

Anyone can help?

Added 8/5/2014 9:31:42 PM

I think it was flagged because its asking for a good rating. I edited it out and confirm.

Added 8/5/2014 11:03:30 PM

1) x – 8x + 15x show work please User: 2) 15xy3 – 24xy3 + 9xy3 **Weegy:** 15xy3 ? 24xy3 + 9xy3 = (15-24+9)xy? = 0 **User:** 3) 3a + 6(b – 8) **Weegy:** how may I help you? **User:** 3a + 6(b – 8) (More)

Question

Not Answered

Updated 7/8/2014 12:31:33 AM

3 Answers/Comments

x – 8x + 15x = -7x + 15x = 8x

Added 7/8/2014 12:30:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/8/2014 12:33:13 AM]

15xy^3 – 24xy^3 + 9xy^3 = -9xy^3 + 9xy^3 = 0

Added 7/8/2014 12:31:08 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/8/2014 12:33:27 AM]

3a + 6(b – 8) = 3a + 6b - 48

Added 7/8/2014 12:31:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/8/2014 12:33:43 AM]

simplfy 3a + 6(b – 8) please show work
**Weegy:** 3a + 6(b - 8);
=3a + 6b + 6(-8);
=3a + 6b - 48 (More)

Question

Expert Answered

Updated 11/8/2014 1:43:04 PM

1 Answer/Comment

7 + 5(62) – 30 please show work **Weegy:** Ask your question please **User:** 7 + 5(62) – 30 **Weegy:** 7+5 = 12
12*62 = 744
744-30 = 714 (More)

Question

Expert Answered

Updated 5/30/2014 8:47:32 AM

1 Answer/Comment

7 + 5(62) – 30;

7 + 310 - 30;

317 - 30 = 287

7 + 310 - 30;

317 - 30 = 287

Added 5/30/2014 8:47:31 AM

This answer has been confirmed as correct and helpful.

Applying PEMDAS, simplify these expression 10 + 6 (18 ÷ 2 ) – 7

Question

Not Answered

Updated 7/17/2012 1:25:33 AM

1 Answer/Comment

10 + 6 (18 ÷ 2 ) – 7 = 10 + 6 (9) - 7 = 10 + 54 - 7 = 57.

Added 7/17/2012 1:25:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/2/2014 11:51:00 AM], Rated good by andrewpallarca

27,000,902 questions answered

There are no comments.